Planter bench on roof type 1 & 2 (Archi & structural) (RFA-499_Rev B) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF & DWG version of drawings.